Modelling of mass transfer kinetics of sapota (Achraszapota) in ternary solutions of sugar and calcium salt during osmotic dehydration. (16th March 2020) - Shalini, Rachana; Saxena, Alok; Shakya, B.R.
The mass transfer kinetics of sapota in ternary solution was studied at an optimised condition derived using the Box-Behnken design of response surface methodology (RSM). The optimised conditions were found for minimising solid gain and water activity and maximising water loss, weight reduction and overall acceptability. The osmotic dehydration kinetics data were fitted in viz. the Magee model, Page's model and Azuara model. In a comparative study of mass transfer kinetics of sapota between three models viz. the Magee model, Page's model and Azuara model. Page's model was found to fit more effectively to Sapota, for the prediction of water loss and solid gain kinetics during the osmotic dehydration.The simplified solution of Fick's second law of diffusion for a slab geometry was used to calculate the average values of apparent diffusion coefficient ( Deff ), namely 4.49 × 10 −08 m 2 /s for WL and 4.27 × 10 −08 m 2 /s for SG.